Hubungan Umur Kawin Pertama, Penggunaan Kontrasepsi dan Fertilitas Remaja dengan Pendidikan Remaja Wanita - Dismo Katiandagho; Budi Setiawan; Daniel Hamonangan; Agustien Mamahit (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2022)
Background: The purpose of the study was to determine the relationship between adolescents' first mating age, contraceptive use and adolescent fertility with women's education Method: This was an analytical observational study with a cross-sectional study design, independent variables are the age of first marriage, the use of contraception and adolescent fertility and the dependent variable is female education. The population and samples in this study are data from the Performance Survey and Accountability Program (SKAP) KKBPK BKKBN North Sulawesi Province in 2018. The data from the study were analyzed univariately and bivariately using the Correlation test. Results: Statistical test proved that there is a meaningful relationship between the first marriage age of adolescents and the education of adolescent women, with a p value = 0.008, correlation value = 0.736 which has a strong correlation level between first marriage age and female education, there is a meaningful relationship between contraceptive use and female adolescent education, who obtained a p value = 0.019 correlation value = 0.843 which has a strong correlation level between The use of contraception with the education of adolescent women and there is a meaningful relationship between adolescent fertility and adolescent education of women who obtain a p value = 0.001 correlation value = 0.911, namely adolescent fertility has a very strong correlation with the level of education of adolescent women. Suggestion: The government needs to pay attention to the implementation of policies on adolescents, especially reproductive health issues, and create effective programs for the distribution of reproductive health information for adolescents.